Comparative Law of Religions in Germany and Austria: Current Situation and Methodological Approaches - Berkmann, Burkhard Josef (Riflessioni di metodo sul diritto comparato delle religioni, 2017)
This contribution provides a description of the state of the art of the studies and the teaching of comparative law of religions and a discussion of the different methodological approaches to this field of research. In the third section of the contribution the peculiarities of the comparison of religious laws are taken into consideration, highlighting the difference with the comparison of secular legal systems. It is also discussed to what extent the principles developed for interreligious dialogue can be applied to the comparison of religious laws.